The Relationship of Stress Levels and Menstrual Cycle among Female Students - Shinta Novelia; Siti Syamsiah; Wisnel Wenola (KHD Production, 2023)
Students as academic individuals cannot be separated from stress in everyday life. Academic activities, especially assignments and external demands on oneself, can create stress among female students. Perceived stress can cause the pituitary to release ACTH (Adrenocorticotropic Hormone), increasing cortisol levels and disrupting the menstrual cycle. This study aims to determine the relationship between stress and the menstrual cycle in female students at the Faculty of Health Sciences, Universitas Nasional. The method used is quantitative with an analytical design and uses a cross-sectional design. The sampling technique used random sampling. The sample in this study was 150 respondents. The PSS-10 questionnaire and menstrual cycle questionnaire were used to collect data. Out of the 150 respondents, there were 7 respondents (4.7%), female students of the Faculty of Health Sciences, Universitas Nasional, who experienced everyday stress and 45 respondents (30%) experienced mild stress, and 97 respondents experienced moderate stress (64.7%), 1 respondent (0.7%) experienced severe stress, and out of 150 respondents there were 114 respondents (76%), female students of the Faculty of Health Sciences, Universitas Nasional experienced normal menstruation and 36 respondents (24%) experienced abnormal menstruation. There is no significant relationship between stress levels and menstruation in female students at the Faculty of Health Sciences, Universitas National, with p=0.811. Researchers suggest that female students who experience stress and menstrual disorders can relax by doing Yoga.